(3GdehGba GdNeShf Yf GdfHi (B( (3U(B)s
(3ChdgG (B:s
(3CNHQfG GdbGVi GdCLd GdYGde GHf CHj GdfLe bGd (B: (3cfJ LGdSkG YfO Ydi Hf CHj WGdH (B( (3ef (B) (3hYfOg YHO Gddg Hf YHGS hMhdg s
(3BNQgG (B:s
(3dge ajgG aGcgI , hdge eG jOYhf Je GdehGba GdNeShf HMeO Gddg hefg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdYGTQs
(3cJHJ GdYfGhjjf HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs